Little fires everywhere [compact disc, unabridged] - Ng, Celeste (Penguin Audio ; Books on Tape, 2017)
In Shaker Heights, a placid, progressive suburb of Cleveland, everything is planned - from the layout of the winding roads, to the colors of the houses, to the successful lives its residents will go on to lead. And no one embodies this spirit more than Elena Richardson, whose guiding principle is playing by the rules. Enter Mia Warren - an enigmatic artist and single mother - who arrives in this idyllic bubble with her teenaged daughter Pearl, and rents a house from the Richardsons. Soon Mia and Pearl become more than tenants: all four Richardson children are drawn to the mother-daughter pair. But Mia carries with her a mysterious past and a disregard for the status quo that threatens to upend this carefully ordered community. When old family friends of the Richardson's attempt to adopt a Chinese-American baby, a custody battle erupts that dramatically divides the town--and puts Mia and Elena on opposing sides. Suspicious of Mia and her motives, Elena is determined to uncover the secrets in Mia's past. But her obsession will come at unexpected and devastating costs. Little Fires Everywhere explores the weight of secrets, the nature of art and identity, and the ferocious pull of motherhood - and the danger of believing that following the rules can avert disaster.